Applying Auction Theory to Economics. - Klemperer, P (Department of Economics (University of Oxford), 2000)
This is a preliminary draft of an Invited Symposium paper for the World Congress of the Econometric Society to be held in Seattle in August 2000. We discuss the strong connections between auction theory and "standard" economic theory, and argue that auction-theoretic tools and intuitions can provide useful arguments and insights in a broad range of mainstream economic settings that do not, at first sight, look like auctions. We also discuss some more obvious applications, especially to industrial organization.